Perbandingan Waktu Proses Perencanaan Gedung Bertingkat Antara Menggunakan Dynamo dan Metode Konvensional pada Revit - Yoga Kencana; Toriq Arif Ghuzdewa; Akhmad Aminullah (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2025)
Building Information Modeling (BIM) is a computer-based technology that facilitates planning activities across various disciplines, including structural, architectural, and mechanical–electrical works. The implementation of BIM in construction projects requires a high level of accuracy to ensure cost efficiency and smooth workflow. This study aims to examine the time differences in material calculation processes using two different methods: the conventional Material Take-Off feature in Autodesk Revit and a custom plug-in developed using Dynamo. The study employs a 3D model of a three-story building as the test object. Work duration was measured using a stopwatch at the beginning of each calculation process to obtain more precise time records. The results indicate that the use of Dynamo significantly accelerates the calculation process, achieving a fivefold speed improvement compared to the conventional Material Take-Off method. Furthermore, the developed Dynamo script can be applied to projects of the same type but with different geometric forms. Therefore, the proposed script is expected to serve as a practical solution for enhancing accuracy and productivity in concrete work planning for BIM-based construction projects.